The tadpole of Hylodes caete (Anura: Hylodidae), an endemic Atlantic rainforest Torrent frog of Brazil - Malagoli, Leo R.; de Sá, Fábio P.; Canedo, Clarissa; Haddad, Célio F. B. (Zootaxa, 2020)
The genus Hylodes Fitzinger currently comprises 26 species of Torrent frogs, organized into four morphological taxonomic groups (Heyer 1982; Frost 2020): Hylodes glaber, H. lateristrigatus, H. mertensi, and H. nasus groups. Hylodes lateristrigatus is the most speciose group, comprising today 20 known species (Frost 2020). Nested in this group, a clade has been recovered based on molecular evidence, gathering the only four Hylodes species that are known to have males with nuptial thumb tubercles (de Sá et al. 2015; Malagoli et al. 2017). This well-supported clade includes H. phyllodes Heyer & Cocroft, Hylodes fredi Canedo & Pombal, H. pipilans Canedo & Pombal, and H. caete Malagoli, de Sá, Canedo & Haddad. Among these four Torrent frogs, tadpoles are unknown only for the most recently described H. caete (see tadpole descriptions in Heyer et al. 1990; Laia et al. 2010; Nogueira-Costa et al. 2019). With important taxonomic and conservation implications for the family Hylodidae (Laia & Rocha 2012), we describe here the tadpole of Hylodes caete, a species endemic to the crests and slopes of Serra do Mar, State of São Paulo, southeastern Brazil (Malagoli et al. 2017). The present description is particularly important because, in its type-locality, H. caete occurs in sympatry and syntopy with H. phyllodes (Malagoli et al. 2017).